Implementation of Agrarian Minister's Circular Letter No. B/HR.01/839/IV/2023 Concerning Death Decisions as a Requirement for First-Time Land Registration Aapplications and Maintenance of Land Registration Data (Study at the Blitar Regency Land Office) - Muhammed Sadam Yudha Laksana (Journal of Law, Politic and Humanities, 2025)
In carrying out the registration of land rights, either through buying and selling or changing the name of the heir, if the right holder dies, the name must be changed. In 2023, Minister of Agrarian Affairs circular No. B/Hr.01/839/Iv/2023 Regarding Death Certificates as a Requirement for First-Time Land Registration Applications and Maintenance of Land Registration Data. So the question is what if the person dies a long time ago and their domicile is not known, what if the death certificate is not valid, it must be a death certificate in the transfer of land rights and land registration for land history Letter C 1960. Problem formulation: Effectiveness of Implementation of Minister of Agrarian Affairs Circular No. B/HR.01/839/IV/2023 Regarding the Death Certificate as a Requirement in the First Time Land Registration Application and Maintenance of Land Registration Data at the Blitar Regency Land Office and the Consequences and Obstacles Faced by the applicant in the name change process following the Minister of Agrarian Circular Letter No. B/HR.01/839/IV/2023 at the Blitar Regency Land Office. This research uses empirical methods with conceptual and sociological approaches. The results of the research are the effectiveness of implementing the Minister of Agrarian Affairs Circular No. B/HR.01/839/IV/2023 Regarding Death Certificates as Requirements for Applications for First Time Land Registration and Maintenance of Land Registration Data at the Blitar Regency Land Office is not running effectively because many applicants' files for registration of land rights they own are having problems in fulfilling the completeness of the documents. the death certificate, especially if the purchase has already occurred and the owner has died and has moved from the area.